Improved prenatal diagnosis of methylmalonic acidemia: mass fragmentography of methylmalonic acid in amniotic fluid and maternal urine - Trefz, Friedrich K.; Schmidt, H.; Tauscher, Bernhard; Depène, E; Baumgartner, R.; Hammersen, Gerhard; Kochen, Walter (European journal of pediatrics, 1981)
A sensitive and reliable method for trace analysis of methylmalonic acid in amniotic fluid and urine is described using deuterated methylmalonic acid as the internal standard and capillary gas chromatography/mass fragmentography. The application of the method for the prenatal diagnosis of methylmalonic acidemia is demonstrated in three pregnancies at risk. In two pregnancies the fetuses were affected by methylmalonyl-CoA-mutase deficiency. Correspondingly, the excretion of methylmalonic acid in the maternal urine was elevated as early as at the 12/13th week of gestation, reaching its highest level shortly before abortion at the 19/20th week: 157 and 173 μmol/24h (excretion in normal pregnancies: 39±8 μmol/24h, n=8). In addition, the concentration of methylmalonic acid in amniotic fluid at the 16th week (13.4 and 33.8 μmol/l, normal range 0.31±0.10μmol/l, n=8) strongly suggested that the fetuses were affected. In the third pregnancy no increase of the methylmalonic acid excretion in maternal urine at 11-17 weeks of gestation could be found (42±10 μmol/24h, n=5). The cultured amniotic cells of this fetus showed normal enzyme activity. Nevertheless abortion was initiated without further biochemical investigation because of an elevated a1-fetoprotein value in the amniotic fluid. The fetus was anencephalic. The data suggest that it is possible to make a reliable prenatal diagnosis of methylmalonic acidemia even in those cases where cultured amniotic cells are not available.
Gesehen am 16.12.2025